2011
DOI: 10.1073/pnas.1111963108
|View full text |Cite
|
Sign up to set email alerts
|

Genomic dissection of the epidermal growth factor receptor (EGFR)/PI3K pathway reveals frequent deletion of the EGFR phosphatase PTPRS in head and neck cancers

Abstract: Activation of the PI3K and epidermal growth factor receptor (EGFR) pathway is able to drive oncogenesis in multiple human cancers, including head and neck squamous cell carcinoma. Targeted agents such as cetuximab and erlotinib are currently used in patients with head and neck squamous cell carcinoma, but, in this disease, the genomic alterations that cause pathway activation and determine response to pharmacologic inhibition remain ill-defined. Here, we present a detailed dissection of the EGFR/PI3K pathway, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 47 publications
3
91
0
1
Order By: Relevance
“…These findings were in line with evidence that EGFR participated in the PTPRS-regulated PI3K/protein kinase B-signaling pathway. 18 However, alterations of PTPRS expression resulted in phosphorylation changes of multiple RTKs, as revealed by PTK array, suggesting that other potential direct/ indirect substrates of PTPRS need further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings were in line with evidence that EGFR participated in the PTPRS-regulated PI3K/protein kinase B-signaling pathway. 18 However, alterations of PTPRS expression resulted in phosphorylation changes of multiple RTKs, as revealed by PTK array, suggesting that other potential direct/ indirect substrates of PTPRS need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, loss of PTPRS had been reported in head and neck carcinoma and closely related to chemotherapy resistance. 18 However, PTPRS expression pattern, derived from TCGA database (Supporting Fig. 1), in several types of human cancer indicated that a tumorspecific investigation on the role of PTPRS was required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, PTPR proteins are mutated with a 30% frequency across 15 types of solid tumors (29). Second, PTPRS is specifically microdeleted in 26% of head and neck cancer patients (34). Third, PTPRS function is modulated by shedding (35) suggesting that its tumor suppressor activity could be abrogated by ADAM17-mediated shedding.…”
Section: Discussionmentioning
confidence: 99%
“…2 In this study, which acts as an example of the application of comparative genome hybridisation arrays in head and neck cancer, several alterations in the EGFR/PI3K pathway were identified, including novel microdeletions in the PTPRS gene.…”
Section: Comparative Genome Hybridisation Arraysmentioning
confidence: 99%